Historical Analysis: Contemporary Image and Representation of Sultan Muhammad Bin Tughlaq Among Ziauddin Barani’s Texts - Wafiullah Aminzai; Dadman, Enayatullah (International Journal of Contemporary Sciences (IJCS), 2023)
One of the most important domain in human knowledge is Historiography which donate a lot theory in the field, the two most well-known schools are the Persian and Arab historiographies. The Arab historiography is the first. From the time when Islam was established in India at the beginning of the 13th century until the great Mughal Empire fell, two significant contributions to the development of Persian history in India during the Sultanate Period, notably during the authority of the Tughluq dynasty, are the "Tarikh-i- Firuj Shahi" of Barani and the "Futuhus Salatin" of Isami, The present paper focus on contemporary image of Sultan Mohammad Bin Tughluq among Zia ud Din Bharani’s Texts. A descriptive context analysis method is used and for the data collection Tarikh-i- Firuj Shahi book was selected, as a result The two masterpieces produced under the patronage of the Sultans of Delhi are thought to be Tarikh-i- Firuz Shahi of Barani. Both novels give us important details about the era in which they were written